Processos de racialização nas escolas primárias pernambucanas (1911-1945) - Arantes, Adlene Silva (2014)
We seek in this thesis to analyze the practices of racialization to which primary school children were submitted in Pernambuco in the period 1911-1945. We adopted this period for its reference to the initial moment of institutionalization of primary schools in Pernambuco, while the milestone relates to the end of Estado Novo, which was marked by a more pronounced concern of the Brazilian state in relation to the definition of "figure of the Brazilian man." Therefore, many anthropometric studies were drafted aiming at establishing the biotype of Pernambuco school. These studies were intended to create homogeneous school classes both physically and intellectually. Thus, discussions around the hygienism and eugenic thinking ended up entering the school environment from the requirements and regulations that quite possibly came to influence the school routine, thus marking singularities of school culture specially in the context of elementary schools. Based on discussions, often racialized, intellectual and political elite sought to biologically explain the underdevelopment that Brazil was going through. Therefore, the proposal pointed out that the situation was the harmonization of a national type, through the "whitening" of Brazilian society, sometimes more veiled, sometimes more explicit. We revisited racial theories to define this model of man as we believe that the education policies reflected these ideas. The myth of racial democracy also contributed to strengthening the need for bleaching Brazilian society, this time by this cultural bias and not the biological one. We used as sources: laws, decrees, reports, rules, regulations, and public education reform, education programs in primary schools, reports and papers for elementary school , statistical yearbooks of teaching, governors pronouncements on education, journals of education, medical and general topics, lesson plans, newspapers, thesis of medical area, as well as the iconography and didactic and non-didactic textbooks. All this documentary range was analyzed theoretically and methodologically from the perspective of New Cultural History, approaching more specifically the concept of representation produced by Roger Chartier, besides ethnoratial studies and the history of education in Brazil. The results revealed that the reforms envisioned by Ulysses Pernambucano, Carneiro Leao and Aníbal Bruno in Pernambuco aimed to solve the "Brazilian race problem." To racializing schoolchildren, it was used the rankings compiled by Roquette-Pinto, who took into account skin color, the hue of the eyes and hair characteristics. Associated to this, Psychology and Sociology were applied by professionals involved with education, as it was the case of school physicians, visiting nurses and teachers themselves. We have also seen that the school culture contributed to establish racial distinctions that ensured the progress of the country by educating healthy, regenerated and civilized citizens. We end our study arguing about the role Physical Education had in the national and local scene considering that the policies of racialization based on anthropometric tests and measurements gave us the mission of reinvigorating the breed and ensuring the establishment of a healthy society both physically, intellectually and morally.